Home-to-home dialysis transition: A 24-year single-centre experience. Issue 3 (May 2022) - Elbokl, Mohamed Ahmed; Kennedy, Claire; Bargman, Joanne M; McGrath-Chong, Marg; Chan, Christopher T
Home dialysis (peritoneal dialysis (PD) and home haemodialysis (HHD)) are ideal options for kidney replacement therapy (KRT). Occasionally, because of technique failure, patients are required to transition out of home dialysis, and the most common option tends to be to in-centre HD. There are few published studies on home-to-home transition (PD to HHD or HHD to PD) and dynamics during the transition period. We present a retrospective review of 28 patients who transitioned from a home-to-home dialysis modality at our centre over a 24-year period. We observed a total of 911 home dialysis patients with technique failure (826 PD patients and 85 HHD patients) with only 28 patients (3% of the total with technique failure) having successful home-to-home transition. During the transition period, 11 patients (39%) were hospitalized and 13 patients (46%) required variable periods of in-centre HD. After a median follow-up of 48 months following dialysis modality transition, four patients switched to in-centre HD permanently (home dialysis technique survival of 86% censored for death and kidney transplantation) and four patients died resulting in a patient survival of 86% (censored for switch to in-centre HD and transplantation). In our centre, home-to-home transition is a feasible strategy with comparable patient and technique survival. A significant proportion of patients switching from a home-to-home dialysis modality required variable intervals of hospitalization and in-centre HD during transitions. Future efforts should be directed towards assessment and home dialysis education during the entire process of dialysis transition.